(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
In this work, the synthesis of coordination compounds based on chitosan, which is a natural biopolymer, and their physicochemical properties were studied. Chitosan is understood as the property of a substance to work together with a living organism without causing harm, and simply put, if a substance does not harm the body, does not cause allergies, and is compatible with tissues, it is considered biocompatible, and due to its biodegradability and complex-forming properties, it is widely used in pharmaceuticals, medicine, and ecology. During the study, we studied the mechanism of complex formation of chitosan with metal ions, as well as the analysis of the solubility, thermal stability, and adsorption properties of the resulting compounds. The results obtained show that chitosan-based complexes are promising functional materials, as shown below.